Quantum mechanics for nanostructures - Mitin, Vladimir V.; Sementsov, Dmitry I.; Vagidov, Nizami Z. (Cambridge : Cambridge University Press, 2015)
"The properties of new nanoscale materials, their fabrication and applications, as well as the operational principles of nanodevices and systems, are solely determined by quantum-mechanical laws and principles. This textbook introduces engineers to quantum mechanics and the world of nanostructures, enabling them to apply the theories to numerous nanostructure problems. The textbook covers the fundamentals of quantum mechanics, including uncertainty relations, the Schrödinger equation, perturbation theory, and tunneling. These are then applied to a quantum dot, the smallest artificial atom, and compared to hydrogen, the smallest atom in nature. Nanoscale objects with higher dimensionality, such as quantum wires and quantum wells, are introduced, as well as nanoscale materials and nanodevices. Numerous examples throughout the text help students to understand the material"--Provided by publisher.
"The properties of new nanoscale materials, their fabrication and applications, as well as the operational principles of nanodevices and systems, are solely determined by quantum-mechanical laws and principles. This textbook introduces engineers to quantum mechanics and the world of nanostructures, enabling them to apply the theories to numerous nanostructure problems. The book covers the fundamentals of quantum mechanics, including uncertainty relations, the Schrodinger equation, perturbation theory, and tunneling. These are then applied to a quantum dot, the smallest artificial atom, and compared with the case of hydrogen, the smallest atom in nature. Nanoscale objects with higher dimensionality, such as quantum wires and quantum wells, are introduced, as well as nanoscale materials and nanodevices. Numerous examples throughout the text help students to understand the material"--Provided by publisher.
Machine generated contents note: 1. Nanoworld and quantum physics; 2. Wave-particle duality and its manifestation in radiation and particle's behavior; 3. Layered nanostructures as the simplest systems to study electron behavior in one-dimensional potential; 4. Additional examples of quantized motion; 5. Approximate methods of finding quantum states; 6. Quantum states in atoms and molecules; 7. Quantization in nanostructures; 8. Nanostructures and their applications; Appendices; Index.
Includes index.
Keywords: Quantum theory; Nanostructured materials